In Two Minds of Replacing Life Insurance Policy - Nor Haziah Hashim; Zurina Kefeli@ Zulkefli; Nursilah Ahmad (Universiti Sains Islam Malaysia, 2024)
The case is about how Maju Takaful Resources (MTR), a takaful consultation firm, dealt with their agents' grievances regarding the regulation of Replacement of Policy (ROP) imposed by Bank Negara Malaysia (BNM). The regulation was imposed to curb unwarranted replacement of life insurance policy and to ensure the interest of the policyholders is continuously safeguarded. The regulation specified that agents shall not receive any commission for any policy which is construed as ROP. However, the regulation has placed MTR at a great disadvantage, since most of their clients, whom previously subscribed to conventional life insurance policy wished to switch to family takaful (a shariah-compliant version of life insurance). Unfortunately, according to ROP regulation, these cases were still considered as ROP. The case allowed students to learn the effects of ROP on different stakeholders within the insurance and takaful industries in Malaysia.